Fabrication and characterization of microelectronic devices, circuits and systems VI - Radhakrishnan, K. (2008)
Several concurrent subprojects have been undertaken under the main project ?Fabrication and Characterization of Microelectronic Devices, Circuits and Systems VI. This report records the details of two investigations that were performed: The first investigation was on the study of the feasibility of using second harmonic microscopy (SHM) to measure copper concentration and possible diffusion mechanisms at the surfaces and interfaces of microelectronics interconnect structures. The second investigation was on the impact of intentional copper contamination on the performance of MOS devices. Copper contamination impact on device performance from backside and fiontside of wafers were studied. In our work, we have made a prelimirary but successful attempt to study Cu diffusion at surfaces and interfaces of microelectronic interconnect structures by measuring the optical second harmonic signal generated due to the presence of copper. In both cases, diffusion through barrier bulk and along surfaces and interfaces, SH signal responded to the changes in Cu concentration at elevated temperatures. The signal changes are attributed to copper diffusion either along the bulk tantalum for the non- spatial diffusion study or the interfaces and surfaces of samples for the spatial diffusion study.